Surveillance diagnostic algorithm using real-time PCR assay and strain typing method development to assist with the control of C. auris amid COVID-19 pandemic - Contreras, Deisy A.; Morgan, Margie A. (Frontiers in Cellular and Infection Microbiology, 2022)
Candida auris continues to be a global threat for hospitals. COVID-19 has rerouted the attention and resources of this silent pandemic to the frontlines of this respiratory disease. Cases continue to be on the rise and clinical laboratories need a contingent plan to combat an imminent outbreak amid an ongoing pandemic. Here, we introduce a two-tier Candida auris surveillance program that includes a rapid qualitative RT-PCR for the identification of high-risk patient population being admitted from SNF, LTACH or patients that are ventilated. Secondly, isolated C. auris specimens will get further process for clonal relatedness analysis using the IR Biotyper. We have done surveillance over 700 at risk patients being admitted into the hospital and have identified 28 positive specimens over a one-year period. Clonal relatedness analysis by the IR Biotyper when supplemented by whole genome sequencing (WGS) has shown grouping of two significant clusters which has proven to map to circulating lineage associated with Clade III and Cluster 2 belong to a different clade further supporting the ongoing geospatial C. auris outbreak. Overall, clinical laboratories having the ability to rapid screen at high-risk patients and further doing outbreak investigations by strain typing will aid in the control of C. auris within the hospital setting.